A Microcontroller-based Fish Drying System for Enhanced Drying Time with Real-Time Environmental Monitoring - Guerrero, Rainiell; Calapit, Armiel; Ortega, John Mark; Maaño, Ronaldo C.; P. Santonil, Hannah Shamira; B. Canela, Dhon Niño; A. Maaño, Roselyn; P. Cortez, Emelex (JEECS (Journal of Electrical Engineering and Computer Sciences), 2026)
The preservation of fish through drying is a vital practice in coastal regions like the Philippines. Traditional sun-drying methods often suffer from inefficiencies, environmental inconsistencies, and long drying times ranging from 8 to 20 hours. However, existing automated solutions often lack the specific real-time precision required for small-scale costal processing, leading to inconsistent quality. To address these limitations, this study presents the design and implementation of a microcontroller-based fish drying system to enhance drying efficiency through real-time environmental monitoring. The system utilizes an Arduino UNO R3, a DHT22 sensor, infrared heating lamps, and an AC blower fan to maintain a regulated environment between 40°C and 50°C. The microcontroller is the central processing unit, communicating with the sensor to collect real-time temperature and humidity data. This data is used to dynamically control heating elements and ventilation, ensuring optimal drying conditions, reducing drying time, and improving product quality. Experimental results demonstrate that the microcontroller-based system significantly enhances the efficiency and consistency of the drying process to just 3.51 hours compared to conventional methods which recorded 4.48 hours. Technical evaluation through unit and system testing confirmed the system’s reliability in maintaining a 45° indicator. Stakeholders evaluated the prototype using a 5-point scale, resulting in an overall scientific and functional rating of 4.32 (Strongly Agree). This innovation offers a scalable solution for small-scale processors to improve productivity, quality, and production of dried fish products.